2006
DOI: 10.4049/jimmunol.176.11.6900
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Adapts to a Retrocyclin with Cationic Amino Acid Substitutions That Reduce Fusion Efficiency of gp41

Abstract: Retrocyclin (RC)-101 is a cationic θ-defensin that inhibits HIV-1 entry. Passaging HIV-1BAL under selective pressure by this cyclic minidefensin resulted in only a 5- to 10-fold decrease in viral susceptibility to RC-101. Emergent viral isolates had three amino acid substitutions in their envelope glycoprotein. One was in a CD4-binding region of gp120, and the others were in the heptad repeat (HR) domains of gp41 (HR1 and HR2). Each mutation replaced an electroneutral or electronegative residue with one that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 30 publications
5
74
0
1
Order By: Relevance
“…The mechanism of inhibition of HIV-1 entry by retrocyclin-1 revealed in this study is very similar to that exhibited by N-and C-peptides derived from the HIV-1 gp41 N-HR and C-HR, including the only fusion inhibitor approved by the FDA for antiretroviral treatment (T-20 or enfuvirtide). Further confirmation of this mechanism has been provided by recent studies of in vitro selection of HIV-1 resistance to retrocyclin-1 (46). This study reports that passaging HIV-1 under selective pressure by RC-101, a retrocyclin analog, results in a 5-10-fold decrease in viral susceptibility to RC-101.…”
Section: Discussionsupporting
confidence: 59%
“…The mechanism of inhibition of HIV-1 entry by retrocyclin-1 revealed in this study is very similar to that exhibited by N-and C-peptides derived from the HIV-1 gp41 N-HR and C-HR, including the only fusion inhibitor approved by the FDA for antiretroviral treatment (T-20 or enfuvirtide). Further confirmation of this mechanism has been provided by recent studies of in vitro selection of HIV-1 resistance to retrocyclin-1 (46). This study reports that passaging HIV-1 under selective pressure by RC-101, a retrocyclin analog, results in a 5-10-fold decrease in viral susceptibility to RC-101.…”
Section: Discussionsupporting
confidence: 59%
“…Drug dependence is a relatively rare phenomenon in HIV-1 drug resistance. T20-or retrocyclin (RC101)-dependent viruses that involve a combination of substitutions in the HR1 binding site of the inhibitors and in HR2 have been described (44,45). The T20-dependent V549A/N637K virus did not show cross-resistance to or dependence on VIR165 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Drug dependence can be classified as a special form of resistance, since the virus is able to replicate in the presence of the drug but the resistance mutations cause a severe replication defect in the absence of drug, which can only be overcome by addition of the drug. This phenomenon has been described for only a limited number of cases, although drug stimulatory effects and drug dependence were reported for several HIV-1 inhibitors targeting the Gag, protease, and Env proteins (44,45,(61)(62)(63). For Env, enhanced fusion kinetics can render HIV-1 resistant to fusion inhibitors (decreased opportunity), but "hyperfusogenic" Env variants can become dependent on the drug to avoid a premature HR1-HR2 collapse in the absence of a target membrane (44,45,59).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have also revealed that retrocyclin analogs can remarkably protect CD4 + T cells against infection by clinical isolates of HIV-1 from a number of different clades 80 and induce very little resistance in HIV-1. 81 Retrocyclins are highly effective in the presence of human vaginal fluid, 82 are not proinflammatory, 38,82 and can prevent organotypic cervicovaginal tissues from HIV-1 BaL infection. Moreover, retrocyclins exhibited little to no hemolytic activity nor cytotoxicity against H9 cells and ME-180 cervical carcinoma cells at up to 500 lg ⁄ mL, a concentration that far exceeds the amount required for complete protection against most strains of HIV-1 (2-10 lg ⁄ mL).…”
Section: Bacterial Vaginosis Causes Dysfunction In Innate Immunity Ofmentioning
confidence: 99%